Enabling decentralized transshipment in waterborne container transportation - Cyril Alias; Helmut Broß; Jonas zum Felde; Dieter Gründer (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: This research aims at developing a comprehensive transshipment solution leading to additional opportunities of transshipment from small inland vessels throughout the West German canal network and, thereby, extending the existing capacities consisting of container bridges and reach stackers. Methodology: The cargo flows between the major western seaports in Belgium and the Netherlands and relevant hinterland destinations in the West German canal network were analyzed and complemented by spatial analyses of potential transshipment points and their respective facilities. Based on this, the design process of a mobile transshipment facility has been initiated in order to realize its integration into the decentralized waterborne container transportation network. Findings: On the basis of the framework conditions, an effective transshipment solution in the form of a mobile onboard crane has been developed. Performance data of both the small inland vessels and the newly developed cranes have been generated so that a comparison of the existing alternatives and a performance evaluation have been made possible. Originality: Equipped with the mobile onboard crane, the small inland vessels operating in the designated area are no longer dependent on the transshipment facilities ashore. Comparable projects have either focused on the transport network or the onboard crane exclusively.
urn:nbn:de:gbv:830-882.0162239; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; City Logistics